‘Knowledge Workers’ in the Baltic Sea Region: Comparative Assessment of Innovative Performance of the Countries in the Macro-Region - Kirch Aksel (Baltic Journal of European studies, 2018)
The article studies the problems of human resources stemming from increased mobility, and the emergence of new aspects of migration processes. A comparative analysis of the connection between academic development in the context of university (and the science system) and the process of labour migration taking place in Poland, Latvia, Lithuania and Estonia was carried out. The article examines the limits of the model through European territorial migration process and concludes that the huge migration of high-skilled labour (called the “knowledge workers”) has had a very negative impact on the innovative and academic potential of Poland, Lithuania, Latvia and a negative impact in Estonia. In the final section, the article examines increase in the requirements for competence in the Baltic Sea macroregion of the European Union and Estonia’s university reform of 2013-2016 as an illustrative experiment to (un)resolved problems. The first results of the reform in higher education indicated that it was ineffective-for students, the good ideas of the reform proved to be a lost experiment and the mobility of knowledge workers, as the future academic resource in homeland, turned from Estonia to larger Europe, especially to Finland and the UK.